Preoperative imaging of Charcot neuroarthropathy - Höpfner, S.; Krolak, C.; Kessler, S.; Tiling, R. (Nuklearmedizin - NuclearMedicine, 2006)
With about 4 million diabetics in germany and presumed inclination over the following years the treatment of diabetic complications like diabetic foot will become an even more important point. The management of Charcot’s foot has undergone fundamental change in the last few years. Formerly, treatment was almost exclusively limited to non surgical measures; since the late 1990’s, however, current practice has shifted to early, stage-appropriate surgical therapy. The aim of the present prospective study was to investigate the value of positron emission tomography (PET) in the pre-operative work-up of Charcot’s foot. PET were compared to magnetic resonance tomography (MRI). Patients, methods: MRI and PET imaging were used as part of the preoperative work-up in 18 patients with Type II diabetes mellitus. The diagnosis of Charcot’s foot requiring surgical treatment were made on the basis of clinical and radiologic criteria. Results: Of 46 Charcot’s lesions confirmed at surgery, 44 and 35 were detected by means of PET and MRI, respectively. PET can be used in the work-up of patients with metal implants where the MRI does not show adequate findings. PET shows the areas of detritus formation exhibit only moderately increased glucose metabolism and at visual interpretation do not usually impress as typical for acute osteomyelitis. Average SUV values stood at 1.2 (range: 0.5–2.9). Conclusions: The differentiation between Charcot’s lesions and florid osteomyelitis provides the surgeon with important additional information, which is often unavailable from MRI. Because of this important additional data, PET could be considered preferable to morphologic imaging (CT, projection radiography) in the preoperative work-up of Charcot’s foot.
Keywords: Diabetic neuropathic osteoarthropathy; positron emission tomography; magnetic resonance imaging; bone detritus